Strategi Pemberdayaan Masyarakat dalam Pengembangan Jiwa Kewirausahaan (Entrepreneurship) di Dusun Langkan, Desa Landih, Kecamatan Bangli, Kabupaten Bangli - I WAYAN SUI SUADNYANA; I GEDE SETIAWAN ADI PUTRA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Community Empowerment Strategy in Entrepreneurship Spirit Development in Langkan Sub-Village, Landih Village, Bangli District, Bangli Regency Community empowerment as a development concept fulfills social values. One of the efforts is through entrepreneurship development. The community of Langkan Sub-Village, Landih Village, Bangli District, Bangli Regency is a potential area to be empowered in the field of entrepreneurship. Therefore, this study aims to identify internal factors in the form of strengths and weaknesses as well as external factors in the form of opportunities and threats. After getting thesefactors, then the strategy of community empowerment was formulated in the development of entrepreneurship spirit. These factors were analyzed using IFASEFAS analysis, SWOT quadrant analysis, IE matrix, and SWOT matrix. The results showed that the main strength in Langkan Sub-Village is in the form ofavailable agricultural land adequate for the development of entrepreneurship. The main weakness is that there was no association, group or similar businessorganization causing the lack of coordination. The main opportunity is that there were increasingly serious efforts of the government to increase the number ofentrepreneurs both in agriculture and non-agriculture sectors. While the main threat is the flow of world trade that causes losses if they are not able to compete.Through the SWOT analysis quadrant, it can be seen that the community was on a progressive strategy. While the I-E Matrix formula finds the strategy of harvestand divestment. In addition, SWOT matrix analysis found 14 alternative strategies. The most priority strategy is to encourage human resources who are educated, have the skills, have the spirit and the willingness to go forward to follow the competition and the improvement of the entrepreneurial program sothat there is an increase of entrepreneurial competence.